Eating from one pot : the dynamics of survival in poor South African households - Mosoetsa, Sarah; ebrary, Inc. (Johannesburg : Wits University Press, 2011)
"As poverty and unemployment deepen in contemporary South Africa, the burning question becomes, how do the poor survive? This book provides a compelling answer. Based on intensive fieldwork, it shows how many African households are on the brink of collapse. That they keep going at all can largely be attributed to the struggles of older women against poverty. They are the fulcrum on which household survival turns. This book describes how households in two different areas in KwaZulu-Natal are sites of both stability and conflict. As one of the interviewees put it: "We eat from one pot and should always help each other." Yet the stability of family networks is becoming fragile because of the enormous burden placed on them by unemployment and unequal power relations. Many of the households are extremely poor, relying on a total monthly income of less than R800. People live on little more than maize meal, tea and sugar. However, the book also demonstrates that they are not passive victims of poverty. Women, in particular, show impressive qualities of energy and resourcefulness. They engage in a number of informal sector activities, and many are active in a range of faith, and community and home-based care associations"--Publisher's website.
Includes bibliographical references (pages 152-170) and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2015. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Communal living -- South Africa; Poverty -- South Africa; Households -- Economic aspects -- South Africa; Electronic books